2022
DOI: 10.1093/hropen/hoac038
|View full text |Cite
|
Sign up to set email alerts
|

Evidence and consensus on technical aspects of embryo transfer

Abstract: BACKGROUND Ultrasound-guided embryo transfer (US-GET) is a widely performed procedure, but standards for the best practice are not available. OBJECTIVE AND RATIONALE This document aims to provide an overview of technical aspects of US-GET after considering the published data and including the preparation for the embryo transfer (ET) procedure, the actual procedure, the post-procedure care, associated pathologies, complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…The American Society for Reproductive Medicine (ASRM) guidelines describe better pregnancy rates with several measures, such as the use of abdominal ultrasound during the transfer, the removal of cervical mucus, the use of a soft catheter and the deposition of the embryo at about 1–2 cm from the uterine fundus 2 . Recently, D’Angelo et al 3 provided for ESHRE (European Society of Human Reproduction and Embryology) an overview of technical aspects of ET, including the preparation prior to ET, the procedure itself, the post-procedure care, and the importance of the physicians’ performance. Their recommendation overall overlap with those of the ASRM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The American Society for Reproductive Medicine (ASRM) guidelines describe better pregnancy rates with several measures, such as the use of abdominal ultrasound during the transfer, the removal of cervical mucus, the use of a soft catheter and the deposition of the embryo at about 1–2 cm from the uterine fundus 2 . Recently, D’Angelo et al 3 provided for ESHRE (European Society of Human Reproduction and Embryology) an overview of technical aspects of ET, including the preparation prior to ET, the procedure itself, the post-procedure care, and the importance of the physicians’ performance. Their recommendation overall overlap with those of the ASRM.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure of embryo transfer (ET) is unanimously claimed to be crucial for the success of IVF 1 . The procedure should be guided by ultrasound, soft catheters should be preferred, and the embryos should be released at about 1–2 cm from the fundus of the uterus 1 3 . There is also evidence suggesting that concomitant administration of hyaluronic acid (HA), Granulocyte Colony Stimulating Factor (G-CSF), human Chorionic Gonadotropin (hCG), or atosiban may improve the success rate, but the effectiveness of these add-ons remains debated 1 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…However, at the time of writing this paper, there are no guidelines or consensus on blastocyst and cleavage-stage transfers. There is a 2022 consensus on embryo transfer, but the publication was focused on technical aspects before, during, and after the procedure [8]. Several studies have examined the clinical outcomes of the blastocyst-stage transfer but a 2022 Cochrane review concluded that more evidence was needed to determine the impact of the stage of transfer on cumulative live births and pregnancy rates [9].…”
Section: Introductionmentioning
confidence: 99%
“…These factors include the difficulty of embryo transfer, the appearance of blood or mucus, embryo retention, high uterine contraction frequency, the catheter type, catheter loading and placement techniques, ultrasound quality, and operator-related factors. 4 , 5 In order to standardize ET technique, the American Society of Reproductive Medicine (ASRM) guideline recommends using ultrasound guidance and a soft catheter during the procedure, as well as advocates for early ambulation after the procedure. 6 However, minimal attention has been paid to the embryo transfer technique, as embryo transfer is sometimes seen as an insignificant contributor to the outcome of an IVF cycle; furthermore, physicians are usually unwilling to update their routines or methods for performing embryo transfer.…”
Section: Introductionmentioning
confidence: 99%